1994
DOI: 10.1017/s0952523800001681
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal connections between the rabbit suprageniculate pretectal nucleus and the superior colliculus: Tracer study with horseradish peroxidase and fluorogold

Abstract: Connections of the rabbit suprageniculate pretectal nucleus (SP) with the superior colliculus were explored by means of retrograde transport of horseradish peroxidase or Fluorogold. Large injections centered in the superficial and intermediate tectal layers resulted in bilateral retrograde transport to the medium-size multipolar neurons of the suprageniculate pretectal nucleus. Horseradish peroxidase was also transported anterogradely into the ipsilateral and contralateral neuropiles of the suprageniculate pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…3A,B). Histological analysis showed that only the anterior region of the dorsal midbrain, including the anterior-most mes-derived structure, the PPT (Lagares et al, 1994), appeared normal; tissue was missing at the posterior end of the SC; and the IC, dorsal isthmus and vermis were absent ( Fig. 3C-E).…”
Section: Spry2-gof In Mes/r1 or By Reducing Fgf17 And Fgf8 Gene Dosementioning
confidence: 99%
“…3A,B). Histological analysis showed that only the anterior region of the dorsal midbrain, including the anterior-most mes-derived structure, the PPT (Lagares et al, 1994), appeared normal; tissue was missing at the posterior end of the SC; and the IC, dorsal isthmus and vermis were absent ( Fig. 3C-E).…”
Section: Spry2-gof In Mes/r1 or By Reducing Fgf17 And Fgf8 Gene Dosementioning
confidence: 99%
“…Rostrally, all midbrain tissue except the posterior pretectal nucleus (PPT) was absent. Although its name implies that the PPT is of forebrain origin, comparative anatomical studies indicate that it is a midbrain structure derived from the rostral mesencephalon (Lagares et al, 1994). Caudally, no cerebellar tissue was observed, and the locus ceruleus was absent.…”
Section: Deletion Of Mes/met Derivatives Increases In Severity With Pmentioning
confidence: 99%
“…Although a mammalian homolog of SpL has not been definitively identified (Reiner et al, 1984(Reiner et al, , 1998aCaballero-Bleda et al, 1992;Lagares et al, 1994), several lines of evidence indicate that SpL in birds is the target of an additional direct striatal output and is thereby analogous to mammalian GPi (Reiner et al, 1984(Reiner et al, , 1998aMedina et al, 1999). As is true of the GPi-like cell groups in mammals (i.e., GPi itself and SNr), SpL neurons are GABAergic, receive input from SP ϩ striatal neurons as well as from dorsal pallidal neurons that receive ENK ϩ striatal input (i.e., GPe-like pallidal neurons), and are notably enriched in GluR4 (Karten and Dubbeldam, 1973;Reiner et al, 1982aReiner et al, , 1984Veenman and Reiner, 1994;Reiner, 1996, 1997; Pa- Karten and Hodos (1967).…”
Section: Circuitry Of Ala and Stnmentioning
confidence: 99%